Measuring performance : expert solutions to everyday challenges - Kaplan, Robert S. (Pocket mentor series., 2009)
"The Pocket Mentor series offers immediate solutions to the challenges managers face on the job every day. Each book in the series is packed with handy tools, self-tests, and real-life examples to help you identify strengths and weaknesses and hone critical skills. Whether you're at your desk, in a meeting, or on the road, these portable guides enable you to tackle the daily demands of your work with greater speed, savvy, and effectiveness. Organizations want-and need-to track the changes in their overall performance. And the divisions, units, teams, and individuals within these organizations engage in similar success measurement. Performance Measurement explains the importance of regularly monitoring your group's performance and introduces formal measurement practices. You'll learn to: Apply a disciplined process to performance measurement ; Set targets and communicate data effectively ; Use performance management as a coaching and development tool.